2013
DOI: 10.1590/s1679-45082013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da postura e dos movimentos articulares dos membros superiores de pacientes pós-mastectomia e linfadenectomia

Abstract: Objective:To evaluate alterations in posture and range of motion of the upper limbs in women after mastectomy and lymphadenectomy, submitted to radiotherapy as adjuvant treatment.Methods:Two groups were evaluated: 16 post-mastectomy women with lymphedema of the upper limb and 14 post-mastectomy women without lymphedema. Patients were submitted to analysis made by software, one for posture and the other to measure ranges of movement of the shoulder, elbow, and wrists. The results obtained were compared between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 11 publications
1
16
0
7
Order By: Relevance
“…The evaluation was conducted through observation, using as a benchmark the posturography test in which the individual is wearing swimsuits and barefoot. (34) j) Clinical Posturogram was used in 1 study: Haddad et al (36) . Posture assessment was performed with the capture of six images with the individual in orthostatic position (ventral and back sides, left and right profile) and anterior trunk flexion (anterior and lateral views).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation was conducted through observation, using as a benchmark the posturography test in which the individual is wearing swimsuits and barefoot. (34) j) Clinical Posturogram was used in 1 study: Haddad et al (36) . Posture assessment was performed with the capture of six images with the individual in orthostatic position (ventral and back sides, left and right profile) and anterior trunk flexion (anterior and lateral views).…”
Section: Discussionmentioning
confidence: 99%
“…For range of motion assessments were checked: surface projection of the center of the glenohumeral joint laterally; greater and lesser tubercle of the humerus; center of the olecranon; styloid process of the ulna; acromion; surface projection of the center of the elbow joint; center between radius and ulna distally). (36) Considering the analysis methods used, it can be seen that there was no uniformity in the choice of the method for the evaluation of body position. However, it was found that most of the reviewed studies used PAS (5,11,13,15,18,19,23,25,26,(29)(30)(31)33,35,37) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioterapia, quimioterapia, hormonioterapia, bem como a mastectomia -ressecção do tumor, que pode ser do tipo conservadora ou radical, essa última quando associada à linfonodectomia axilar -, são os tratamentos indicados para o câncer de mama, obtendo-se bons resultados na sobrevida e qualidade de vida dessa população. 1,3 Contudo, quando há retirada dos linfonodos axilares, junto com o tratamento de radioterapia pós-operatória, aumenta-se o risco de desenvolver o linfedema de braço, que é uma complicação comum e que interfere diretamente no cotidiano e na qualidade de vida desses indivíduos 3 . O linfedema de braço é definido como acúmulo de líquido, altamente proteico e de origem linfática, nos espaços intersticiais, determinado por deficiência na absorção ou condução da linfa.…”
Section: Introductionunclassified
“…Ele prejudica seriamente as atividades sociais e pode gerar depressão e ansiedade, não permitindo que se esqueça do sofrimento causado pela doença e seu tratamento 6 . O linfedema, portanto, pode ser considerado como doença crônica e apresenta como principais complicações: edema, fibrose pós-radioterapia, mobilidade restrita e dor 3 . Além disso, a presença da proteína no espaço intersticial pode aumentar o risco de infecção, tumores, ferimentos e diminuir a capacidade de regeneração tecidual 4,7 .…”
Section: Introductionunclassified